Isolation and characterization of polyhydroxyalkanoate producing bacteria from legume rhizosphere soils in Me Linh commune, Hanoi - Nguyen, Kim Thoa; Lai, Thi Hong Nhung; Phan, Thi Tuyet Minh; Hoa, Thi Minh Tu; Tran, Thanh Thuy; Nguyen, Quoc Viet; Nguyen, The Trang; Do, Thi Thanh Trung; Le, Tat Thanh (Vietnam Journal of Biotechnology, 2025)
The increasing demand for sustainable bioplastics has driven the search for polyhydroxyalkanoate (PHA)-producing microorganisms from diverse ecological niches. In this study, we isolated and characterized native soil bacteria with the ability to accumulate PHAs from the rhizosphere of leguminous crops in Me Linh commune, Hanoi. A total of 206 bacterial isolates were obtained from eight soil samples and screened for intracellular PHA granules using Sudan Black B and Nile Blue A staining. Of these, 21 isolates tested positive for PHA accumulation, and five strains (ML53, ML71, ML91, ML113, and ML205) were selected for further analysis. Quantitative fermentation experiments revealed that strains ML113, ML91, and ML71 achieved the highest PHA contents, ranging from 20.7% to 24.8% of dry cell weight (DCW). Fourier-transform infrared (FTIR) spectroscopy confirmed the presence of functional groups characteristic of PHB and PHBV biopolymers. Morphological, biochemical, and molecular analyses—particularly 16S rRNA gene sequencing and phylogenetic tree construction—revealed that the selected isolates belong to three distinct genera: Pseudomonas (ML53, closely related to P. putida), Micrococcus (ML91, closely related to M. luteus), and Priestia (ML71 and ML205, clustered with P. megaterium, and ML113, closely related to P. aryabhattai). The results highlight the legume rhizosphere as a rich source of genetically diverse and metabolically competent PHA-producing bacteria with promising potential for future bioplastic development.